2008
DOI: 10.1007/s11270-008-9804-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Bentazon and Molinate on Anabaena cylindrica, an Autochthonous Cyanobacterium of Portuguese Rice Field Agro-ecosystems

Abstract: The effects of bentazon and molinate, two selective herbicides recommended for integrated weed management in rice, were studied in Anabaena cylindrica, an abundant cyanobacterium isolated from a Portuguese rice field agro-ecosystem. Comparative effects of both herbicides on A. cylindrica were estimated under laboratory conditions by measuring its dry weight yield, photopigments, and carbohydrate and protein contents in a time-and dose-dependent exposure throughout 72 h. Photosynthesis and respiration were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The study area details of sampled rice fields were similar to those described by Marques et al (2008), and Vela Lake biotic and abiotic characteristics were extensively monitored previously (de Figueiredo et al, 2006). The samples from rice fields and Vela Lake were collected in situ according to the methodologies described in Galhano et al (2009) andde Figueiredo et al (2006), respectively. Cyanobacterial strains were isolated by capillarity, agar plate spreading and serial dilution techniques (Andersen & Kawachi, 2005).…”
Section: Cyanobacterial Isolation and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area details of sampled rice fields were similar to those described by Marques et al (2008), and Vela Lake biotic and abiotic characteristics were extensively monitored previously (de Figueiredo et al, 2006). The samples from rice fields and Vela Lake were collected in situ according to the methodologies described in Galhano et al (2009) andde Figueiredo et al (2006), respectively. Cyanobacterial strains were isolated by capillarity, agar plate spreading and serial dilution techniques (Andersen & Kawachi, 2005).…”
Section: Cyanobacterial Isolation and Culture Conditionsmentioning
confidence: 99%
“…The native strains frequently found in European rice fields mainly belong to the heterocystous genera Anabena and Nostoc, but also Calothrix and Tolypothrix (Whitton, 2000;Ariosa et al, 2006;Galhano et al, 2009). On the other hand, the diversity, ecology and genetic heterogeneity among planktonic Anabaenalike and Aphanizomenon-like morphospecies require a deeper characterization, since there is neither a clear phylogenetic nor a morphological separation (Hindák, 2000;Rajaniemi et al, 2005;Stüken et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In one of those studies, the effects of the two selective herbicides recommended for IWM on rice were laboratory-assessed in Anabaena cylindrica during a short-term experiment of 72 h (Galhano et al, 2009). The results obtained in this work revealed that both herbicides had a pleiotropic effect on the cyanobacterium at the range of concentrations tested (0.75-2 mM).…”
Section: Ecotoxicological Impacts Of Basagran ® (Ai Bentazon) and Omentioning
confidence: 99%
“…Photosynthesis (P m Chl ) and dark respiration (R d Chl ) normalized to Chla were inhibited by both herbicide formulations in a time-and dose-response manner within the experiment time, and higher Ordram concentrations full stopped O 2 evolution after 48 h. Pointing to safety environmental precautions, the findings obtained with our study suggest the reduction or even ban of molinate from the agro-ecosystem rice field because of its strong inhibitory action on soil autochthonous microflora, mainly on the important diazotrophic primary producers, the cyanobacteria. Together with pulse-amplitudemodulation (PAM) fluorimetric routine parameters, namely maximum photosystem II (PS II) quantum efficiency (Fv/Fm), effective quantum efficiency of PS II for a light-acclimated sample (Ф PSII ), and photochemical quenching (qP; proportion of light excitation energy converted to photochemical act by the active PS II reaction centres), part of the results published by Galhano et al (2009) were previously presented to the overall scientific community in the 15 th European Bioenergetics Conference held in Dublin, from 19 to 24 July 2008 (Galhano et al, 2008). Relevant findings related to Basagran and discussed in the meeting are displayed in Figure 1 carpet-plot.…”
Section: Ecotoxicological Impacts Of Basagran ® (Ai Bentazon) and Omentioning
confidence: 99%
“…The effects of soil micro flora following use of pesticides have been a subject of present interest through difference in doses and methods of assessing their effect, make comparisons hard. Studies on the effects of Bentazon and Molinate on Anabaena cylindrica of Portuguese rice field agro-ecosystems have provide extensive research foundations (Galhano et al, 2009). Insect pest make a grave problem in the field of agriculture but indiscriminate use of pesticide in cultivated field, creates deleterious effect to the population of soil micro flora.…”
Section: Introductionmentioning
confidence: 99%